A morphological comparative study of proboscis sensilla between Pierinae and Coliadinae (Lepidoptera: Pieridae) - Yagmur Mengi; Selma Seven Çalıskan (SHILAP)
Pontia edusa (Linnaeus, 1758) and Colias croceus (Geoffroy, 1785 in Fourcroy), which are in different subfamilies within Pieridae, feed on nectar. In this study, we tested the hypothesis that sensilla differ in the subfamily category. For this purpose, we investigated the ultrastructural structure of proboscis and sensilla in Pontia edusa (Pierinae) and Colias croceus (Coliadinae) by scanning electron microscopy (SEM). The composition of the wall of proboscis, their surface structure, the shape and distribution of different types of sensilla were compared. Three sensillum types are located on the proboscises of both species, sensilla chaetica, sensilla basiconica, and sensilla styloconica being most common in Lepidoptera. It was determined that the size and distribution of sensilla and especially the structure of sensilla styloconica differ in two species. The results will contribute to studies on food and proboscis morphology of Lepidoptera, and will also be beneficial in further studies on the significance of proboscis and sensilla structure in classification